Indole alkaloids fusarindoles A–E from marine-derived fungus Fusarium equiseti LJ-1. (December 2022) - Dai, Xiao-Ming; Pan, Hui-Lin; Lan, Wen-Jian; Chen, Liu-Ping; Feng, Gong-Kan; Deng, Rong; Zhu, Xiao-Feng; Li, Hou-Jin
Abstract: Five undescribed indole alkaloids, fusarindoles A–E, together with seven known compounds were obtained from the marine-derived fungus Fusarium equiseti LJ-1. Their chemical structures and absolute configurations were determined by comprehensive analysis of the NMR, HRMS, UV, IR, ECD calculation and single-crystal X-ray diffraction data. The possible biosynthetic pathways of fusarindoles C–E were proposed. The cytotoxicities of eleven compounds, including fusarindoles A–E and six known compounds, against five human cancer cell lines A549, CNE2, SUNE1, HepG2 and QGY7701 were evaluated. Graphical abstract: Five indole alkaloids were obtained from the marine fungus Fusarium equiseti LJ-1 by using amino acid-directed strategy. Image 1 Highlights: Amino acid-directed strategy improves the production of alkaloids metabolites. Five indole alkaloids were obtained from the marine fungus Fusarium equiseti LJ-1. Absolute configurations were determined by ECD and single crystal X-ray diffraction data. The possible biosynthetic pathways were proposed. The cytotoxicity against five human cancer cell lines were evaluated.